Role of Amblyomma lepidum in the transmission of Mycobacterium farcinogenes, the causal agent of Bovine farcy (Journal of Advanced Veterinary and Animal Research, 2015)
The present study was conducted to investigate the role of Amblyomma lepidum in the transmission of Mycobacterium farcinogenes, the causal agent of bovine farcy in Sudan. A total of 22 samples comprising of prescapular, submaxillary, mediastinal, parotid, retropharengeal and pulmonary lymph nodes, and subcutaneous nodules were collected for this study. M. farcinogenes was successfully isolated from the specimens by following traditional bacteriological techniques, and the bacteria were identified using standard biochemical assays, lipid analysis using Thin Layer Chromatography, and duplex Polymerase Chain Reaction. Larvae and nymphs of A. lepidum acquired M. farcinogenes from experimentally infected rabbits, and subsequently transmitted the infection to fresh rabbits within a maximum period of ten weeks. In contrast, adult A. lepidum failed to contract the organism from the infected rabbits; so, trans-ovarian transmission could be ruled out. In conclusion, this study confirmed the trans-stadial transmission of M. farcinogenes through larvae and nymphs of A. lepidum. http://dx.doi.org/10.5455/javar.2015.b84